Cytotoxic and genotoxic activity of phenolic fractions from Ulomoides dermestoides Fairmaire, 1893 (Coleoptera, Tenebrionidae), in HaCat cells - Mendoza-Meza, Dary Luz; España-Puccini, Pierine (TIP Revista Especializada en Ciencias Químico-Biológicas, 2016)
Ulomoides dermestoides (Fairmaire, 1893) is a beetle used in alternative medicine treatments in some South American countries. The objective of this study was to evaluate the cytotoxic and genotoxic effects of phenolic fractions (PF) from U. dermestoides. The PF were separated from crude extracts in acetone (PFAc) and ethanol (PFEtOH). The total phenolic content (TPC) was determined by Folin-Ciocalteu test. Volatile and semi-volatile compounds presents in crude extracts were identified by GC-MS; moreover, phenolic fractions were analyzed by HPLC-MS. The cellular viability, after exposition to phenolic fractions, was determined by Trypan blue exclusion test and MTT reduction assay on immortalized human keratinocyte cell line (HaCat); the degree of DNA damage was detected by alkaline comet-DNA assay. The TPC in PFAc and PFEtOH were: 11.34±0.88 mgGAE/g and 6.52±1.28 mgGAE/g, respectively (mean.dif: 4.951; p value = 0.0000). In both samples, HPLC-MS showed a pseudo-molecular ion [M-H]− at m/z 153, tentatively identified as protocatechuic acid. The results of cytotoxic assays suggest that the viability of HaCat cells depends on the concentration and exposure time of each treatment. Furthermore, the comet assay revealed moderate genotoxic effect after 48 hours of exposure to PFAc (40 to 160 µg.mL-1); cytotoxic/genotoxic activity of this fraction could be related to the higher phenol contents.